Formation of the language identity of a blogger - T.M. Kravtsova, S.V. Olenev, B.E. Kildibekova, Z.K. Kurmanova, (Opción, 2019)
The article presents the results of a study built on a discursive analysis of Russian-language materials from Kazakhstan’s blogs on religious subjects. As a result, authors of blogs allow liberties when discussing religious topics, since for some of them the opinion of representatives of religious institutions is not authoritative, and, consequently, there are a number of materials criticizing the clergy. Based on the analysis of the transformations of precedent phenomena, the study concluded that certain types of linguistic personality lead discursive practices in the blogosphere.